THE EFFECT OF HEPTAGON FRAUD ON FINANCIAL STATEMENT FRAUD WITH MODERATION OF INSTITUTIONAL OWNERSHIP - Aslamy , Ahmad Ali Akbar; Hexana Sri Lastanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2025)
This study aims to examine and analyze the effects of pressure, opportunity, rationalization, capability, ego, ignorance, and greed on financial statement fraud, with institutional ownership as a moderating variable. The research population comprises 112 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period from 2021 to 2023. The sample comprises 42 companies from the basic materials sector, resulting in 126 observations, selected using purposive sampling. Data were obtained from financial statements and annual reports. The analysis employed descriptive statistics, Moderated Regression Analysis (MRA), and t-tests using secondary data. The results indicate that pressure, rationalization, capability, ego, and greed have a positive impact on financial statement fraud, whereas opportunity and ignorance do not. Furthermore, institutional ownership weakens the influence of pressure, rationalization, capability, ego, and greed on financial statement fraud, but does not moderate the effect of opportunity and ignorance. These findings underscore the crucial role of institutional ownership in mitigating the risk of fraudulent reporting. Strengthening institutional oversight through active shareholder participation, promoting long-term investment, and enforcing stronger corporate governance can effectively curb fraudulent practices. This study contributes to the literature on financial fraud by expanding the Fraud Diamond framework with additional behavioral factors. It also offers practical insights for regulators, policymakers, and investors to enhance transparency and accountability, particularly in high-risk.